(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2020)
In this preliminary note is described a new norian reptile, Endennasaurus acu tirostris, found in the Zorzino Limestone, in the small quarry of Endenna, near Zogno in the Bergamo Prealps (Lombardy, N. Italy). The specimen, belonging to a new genus and species, is exposed on ventral side, so that nothing can be said about the skull roof pattern. Nevertheless other characters such as the pattern of the pelvic and shoulder girdle, and of the tarsus allow us to consider this specimen as a Lepidosaur and to put it among the Eosuchia sensu Peyer & Kuhn—Schnyder (1955) awaiting a further more complete study to define better the taxonomic position of Endennasaurus acutirostris.